An Experiment on Consumption Responses to Future Prices and Interest Rates - Wolfgang J. Luhan; Michael W. M. Roos; Johann Scharler (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
We design an experiment to investigate the influence of announced future variations in interest rates and prices on consumption decisions. In an experimental implementation of the discounted utility model, the subjects learn the entire paths of inflation and interest rates prior to deciding on a consumption path. We decompose the total change in consumption that results from changes in either interest rates or inflation rates into anticipation and impact effects. While impact effects are of similar orders of magnitude as in the model, future changes in inflation or interest rates exert substantially smaller effects on current consumption than predicted by the model. – – Wir entwerfen ein Experiment, um den Einfluss zukünftiger Veränderungen von Preisen und Zinssätzen auf Konsumentscheidungen zu untersuchen. Das Discounted Utility Model wird so exakt wie möglich im Labor nachgestellt: Die Teilnehmer erfahren die vollständigen Verlaufspfade von Inflation und Zinsen, bevor sie ihre Konsumpfade festlegen. Die Konsumänderung, die sich aus der Änderung von Inflation und Zinssatz ergibt, spalten wir in einen Antizipations- und einen Impact-Effekt auf. Während die beobachteten Impact-Effekte der Größenordnung der Modellvorhersage entsprechen, haben erwartete zukünftige Veränderungen von Inflation oder Zinssatz wesentlich kleinere Auswirkungen auf den aktuellen Verbrauch als vom Modell vorhergesagt.
Keywords: D91; E21; C91; 330; consumption; saving; intertemporal utility maximization; macroeconomic experiment